Encapsulating anaphors in written interviews published online - Dennis Castanheira; Marcele Mendanha (Revista Falange Miúda, 2023)
This article aims to discuss the use of encapsulating anaphors (cf. CONTE, 1996; PECORARI, 2014) in written interviews published online based on the interface between Text Linguistics (VAN DIJK, 2015) and the North-American Functionalism (GIVÓN, 1995; BARLOW; KEMMER, 2000), sociocognitive and interactional theories. For that, we have collected and analyzed Noun Phrases with an encapsulating role in 10 interviews from the Brazilian websites POPLine and ROCKLine from the years of 2017 and 2018. Our results indicate that there is a relation between the use of the encapsulators and the parts of the interviews.